GAMBARAN MALOKLUSI GIGI TERHADAP KUALITAS HIDUP REMAJA USIA 12-14 TAHUN DI SMP NEGERI 29 SEMARANG - Ahyi Alfia Husna (Indonesian Journal of Dentistry, 2022)
Background: Malocclusion is a condition in which the occlusion of the teeth is not in accordance with the normal condition. The prevalence of malocclusion in Indonesia is still common and quite high. The state of malocclusion not only interferes physically but also mentally so that it can reduce the quality of life. Quality of life is seen from four domains, namely oral symptoms, functional limitations, emotional well-being, and social well-being. The purpose of this study was to describe the state of dental malocclusion in adolescents aged 12-14 years at SMP Negeri 29 Semarang and its relationship to quality of life.Method: It was a cross-sectional study with 75 samples aged 12-14 years that met the research criteria. Retrieving data used the Child Perception Questionnaire for ages 11-14 years (CPQ11-14) which had been translated into Indonesian. The examination ofmalocclusion severity used ICON index (Index of Complexity, Outcome, and Need), anddata analysis used was Rank Spearman correlation test.Results: The results of 75 total samples found that the majority of samples with very mildmalocclusion severity as many as 30 samples (40%) had a good quality of life. There was a significant correlation between dental malocclusion and overall quality of life (p <0.05),in the domain of emotional well-being and social welfare there was a significant relationship (p <0.05), but in the oral symptoms domain and functional limitations there was no significant relationship with malocclusion namely (p-value 0.057) and (p-value 0.061).Conclusion: There was a significant relationship between dental malocclusion and overall quality of life (p>0.05